Analisis Penggunaan Gadget terhadap Perilaku Sosial Remaja di Desa Krandegan Kecamatan Gandusari Kabupaten Trenggalek - Budi Santoso; Dita Hendriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research is motivated by the rapid development of technology in the current era of digitalization, one of which is a gadget that is very common in use in Krandegan Village, Gandusari District, Trenggalek Regency, especially by teenagers who almost always carry their gadgets anywhere. The objectives of this study are 1) Knowing how the social behavior of teenagers due to the use of gadgets in Krandegan Village, Gandusari District, Trenggalek Regency, 2) Knowing how the impact of gadget use on teenagers in Krandegan Village, Gandusari District, Trenggalek Regency. This research uses a descriptive qualitative approach. The data collection techniques used were observation, interview, and documentation. Observation is used to observe the use of gadgets by teenagers in Krandegan Village, Gandusari District, Trenggalek Regency, interviews and documentation are used to dig up information about the problem under study. The results showed that: the use of gadgets in the current era is unavoidable and users must be more able to control their use. However, a technology will always have an impact on its users, both positive and negative impacts. Likewise for teenagers where the use of gadgets has an impact on the social behavior they show everyday, there are several changes in social behavior that appear such as reduced intensity of direct interaction with the environment, too fixated on gadgets when interacting directly with the community, being more closed, the emergence of laziness so that they often forget time, procrastinate work, the level of teenage participation in social activities also decreases.The use of gadgets also has several positive impacts and negative impacts on teenagers such as facilitating communication, accelerating the dissemination of information, as a means of entertainment, facilitating the learning and learning process, expanding the network of friends, making it easier to find work, making it easier for teenagers to shop with e-commerce. While the negative impact is that the intensity of direct interaction is reduced, too fixated with their gadgets, making teenagers more closed, teenagers often procrastinate work and neglect their obligations and responsibilities in the real world, making teenagers lazy in learning, decreasing their sense of concern and empathy for the surrounding environment, reducing the level of youth participation in social activities, the spread of hoax news is increasing, impacting on health and patterns, affecting the family economy and vulnerable to fraud.